The Role of Diet and Hygiene in the Management of Digestive Haemorrhages on Peptic Ulcer Disease - CFP , Rahantasoa Finaritra; C, Andrianjafiarivony; F, Randrianasolo; AT , Rajaonera; LH , Samison (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Introduction: Digestive hemorrhage on peptic ulcer is one of the major digestive emergencies. Therapeutic progress in recent years has been based on the removal of risk factors. Our objective was to evaluate the impact of diet and hygiene on digestive haemorrhage in peptic ulcer disease. Patients and method: Our study was prospective, monocentric, reported on digestive haemorrhages on peptic ulcer over a period of 3 months. The variables studied included: age, gender, toxic and drug habits, diet, and change in a 1-month follow-up. The Epiinfo statistical test analyzed the data. A p-value of less than 0.05 was considered significant. Results: Fifty-two cases were retained at the end of the study. The odds ratio between irregular meal schedules and GI bleeding was OR = 18.90 [4.39 - 81.20]. Dietary habits included: chocolate (15.38%), acidic meals (61.54%), spices (30.77%). Three (5.7%) patients had relapsed. Conclusion: The diet recommended in our study was a diet rich in soluble fiber with proscription of toxic habits. The rate of recurrence after one month of regression was low, however our study was limited by its low statistical power.